2009
DOI: 10.1124/mol.109.061028
|View full text |Cite
|
Sign up to set email alerts
|

Iron Chelator-Mediated Alterations in Gene Expression: Identification of Novel Iron-Regulated Molecules That Are Molecular Targets of Hypoxia-Inducible Factor-1α and p53

Abstract: Iron deficiency affects 500 million people, yet the molecular role of iron in gene expression remains poorly characterized. In addition, the alterations in global gene expression after iron chelation remain unclear and are important to assess for understanding the molecular pathology of iron deficiency and the biological effects of chelators. Considering this, we assessed the effect on whole genome gene expression of two iron chelators (desferrioxamine and 2-hydroxy-1-napthylaldehyde isonicotinoyl hydrazone) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 63 publications
8
47
0
Order By: Relevance
“…These chelator concentrations and this incubation period were used because we previously demonstrated that under these conditions the chelators modulate iron-responsive genes (e.g. transferrin receptor 1 (TfR1) (21,30)). The higher concentration of DFO was implemented due to its limited ability to permeate membranes (33,34).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These chelator concentrations and this incubation period were used because we previously demonstrated that under these conditions the chelators modulate iron-responsive genes (e.g. transferrin receptor 1 (TfR1) (21,30)). The higher concentration of DFO was implemented due to its limited ability to permeate membranes (33,34).…”
Section: Resultsmentioning
confidence: 99%
“…Microarray Processing and Data Analysis-RNA isolation and microarray processing were performed, as described previously (21,31). The Affymetrix Human Genome U133 Plus 2.0 430 2.0 array (Affymetrix, Santa Clara, CA) was used, which assesses Ͼ47,000 transcripts from over 38,500 genes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An attractive explanation, therefore, for NDRG1 up-regulation by NO would be through IRE-IRP interactions. This was ruled out, however, because the stem-loop structure of the 3Ј-UTR of NDRG1 has been previously examined and determined not to show structural similarities to any other known highly conserved IRE structures (58). It was therefore concluded that it would not be capable of binding IRPs (58,59).…”
Section: Nitric Oxide Suppresses Tumor Cell Migrationmentioning
confidence: 99%